A technique to increase protein yield in a rabbit reticulocyte lysate translation system - Maria Anastasina; Ilya Terenin; Sarah J Butcher; Denis E Kainov (BioTechniques)
Rabbit reticulocyte lysate (RRL) is a mammalian cell-free system for protein production. However, one of the limitations of this system is its low protein yield. Inclusion of recombinant virus proteins and specific viral structures on target mRNA could enhance protein production in RRL. Here we show that simultaneous addition of influenza A virus NS1 protein and inclusion of the encephalomyocarditis virus (EMCV) internal ribosome entry site (IRES) in the target mRNA facilitate translation initiation and increase protein yield over 10-fold, improving the translation capacity of RRL.